Immigrant women's experiences of childbirth in Swedish maternity care: a systematic review of the qualitative and quantitative literature - Sahra Saidarab; Melissa Krupic; Lutvo Sporisevic; Ferid Krupic (Medicinski glasnik, 2025)
Aim: To investigate immigrant women's experiences of childbirth in Swedish maternity care. Methods: A systematic search was conducted in PubMed, Embase, CINAHL, and Web of Science for qualitative and quantitative literature on immigrant women's experiences with Swedish maternity care. An inductive thematic analysis generated themes and subthemes. Results: Sixteen studies were included in this research. The three main themes were access to healthcare, professional treatment, and feeling significant in care. Key findings revealed that immigrant women struggled with trauma, difficult interactions with midwives, communication issues, interpreter problems, lack of detailed information, the role of doulas, and future concerns. Conclusion: Immigrant women's experiences of Swedish maternity care were marked by information gaps, ignorance, and disrespect, leading to mistrust and delayed help-seeking. Language barriers with midwives caused misunderstandings. A sense of belonging to Swedish society was crucial for a positive experience. More qualitative research, education in transcultural care, and training in interpreter use are needed to improve maternity care for foreign women.
Keywords: Experience; Immigrant; maternity care; review; women